Comparative Analysis of Risk Premium and Stock Market Returns in Indonesia: A Case Study of Normal and COVID-19 Pandemic Periods - Peni Rahmadani; Adler Haymans Manurung (Publikasi Indonesia, 2024)
This research examines the effect of market risk premium (risk premium) on market returns (JCI). In addition, this study aims to see the effect of premium risk on market returns during the COVID-19 Pandemic. The data used in this study is secondary (JCI data and Deposit Interest Rates) for the period January 2010 – September 2023. The method used in this study is the GARCH method (1.1). The results of this study show a positive and significant influence of risk premium on market returns (JCI). During the COVID-19 Pandemic, risk premiums negatively and significantly affected JCI returns or the Indonesian stock market.